Underwater Acoustic Imaging of the Sea - GRELOWSKA, Grażyna; KOZACZKA, Eugeniusz (Archives of Acoustics, 2014)
Acoustic waves are a carrier of information mainly in environments where the use of other types of waves, for example electromagnetic waves, is limited. The term acoustical imaging is widely used in the ultrasonic engineering to imaging areas in which the acoustic waves propagate. In particular, ultrasound is widely used in the observation of human organs – ultrasonography (Nowicki, 2010).Expanding the concept, acoustical imaging can also be used to presentation (monitoring) the current state of sound intensity distribution leading to characterization of sources in observed underwater region. This can be represented in the form of an acoustic characteristic of the area, for example as a spectrogram.Knowledge of the underwater world which is built by analogy to the perception of the space on the Earth's surface is to be systematize in the form of images. Those images arise as a result of graphical representation of processed acoustic signals. In this paper, it is explained why acoustic waves are used in underwater imaging. Furthermore, the passive and active systems for underwater observation are presented. The paper is illustrated by acoustic images, most of them originated from our own investigation.